Endoscopic debridement of chronic plantar fasciitis with heel spur resection – a prospective cohort study - Patrick Buliński; Bartosz Bartosz; Artur Banach; Pavle Milanovic; Sorin Barbu; Jakub Naczk; Tomasz Piontek (Chirurgia Narządów Ruchu i Ortopedia Polska)
Introduction. Chronic plantar fasciitis is often resistant to conservative treatments. While studies have explored endoscopic debridement with heel spur resection, further evaluation is needed due to limited data.Aim. The challenge of treating recalcitrant plantar fasciitis, unresponsive to nonoperative treatments, has necessitated exploring innovative surgical techniques. This study examines a novel operative method that focuses on endoscopic debriding the pathologically altered tissue in the plantar fascia with heel spur resection, preserving the integrity of the aponeurosis to prevent adverse effects on the foot’s biomechanics. The main objective is to evaluate this technique’s efficacy in reducing pain and improving functional outcomes.Methods and materials. A prospective study was conducted on 18 patients (25 feet) with chronic plantar fasciitis unresponsive to conservative treatment for at least 6 months. The patients underwent endoscopic debridement with heel spur resection between 2013 and 2023 at our orthopedic clinic. Preoperative and postoperative outcomes were assessed using the American Orthopedic Foot and Ankle Score (AOFAS) scale at baseline and 3 and 6 months postoperatively. Statistical analysis included the Shapiro-Wilk test for normality and paired t-tests to evaluate the significance of changes in AOFAS scores.Results. Postoperative assessments showed a significant improvement in AOFAS scores, with the mean score increasing from 52.48 5.93 preoperatively to 90.80 4.93 at 3 months and 92.92 3.65 at 6 months postoperatively (p < 0.001). These findings indicate a substantial reduction in pain and enhancement in functional abilities.Conclusions. Endoscopic debridement of the plantar fascia with heel spur resection is a promising, minimally invasive option for chronic plantar fasciitis unresponsive to conservative treatment. However, due to the relatively small sample size and lack of a control group, further studies with larger cohorts and comparisons to traditional approaches are needed to fully understand its impact on foot biomechanics.